2017
DOI: 10.1007/s12328-017-0733-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute pancreatitis caused by Mycoplasma pneumoniae: an unusual etiology

Abstract: It is well known that the most important etiologies of acute pancreatitis are gallstones and alcohol consumption. Once these causes have been ruled out, especially in young adults, it is important to consider less frequent etiologic factors such as drugs, trauma, malformations, autoimmunity or systemic diseases. Other rare and less well studied causes of this pathology are infections, among which Mycoplasma pneumoniae has been reported to cause acute pancreatitis as an unusual extrapulmonary manifestation. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…Although this association between Mycoplasma pneumonia and AP has been further enriched by Leinikki et al and McMahon, no evidence of infection in pancreatic cells by the organism was identified, drawing the organism as a potential etiology into question [6]. A more recent case report and review of the literature by Lacasa et al in March 2017 provided evidence for patients with AP who had a history of upper respiratory tract infection and positive serum serology for Mycoplasma pneumonia [29]. In his report, Lacasa depended on the rule by Parenti et al [8], formulated in his intensive review about infectious causes of AP, where Parenti states that serological tests alone are not enough and that patients must show characteristic symptoms of the causative organism to avoid false association with AP.…”
Section: Bacterial Causes Of Apmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this association between Mycoplasma pneumonia and AP has been further enriched by Leinikki et al and McMahon, no evidence of infection in pancreatic cells by the organism was identified, drawing the organism as a potential etiology into question [6]. A more recent case report and review of the literature by Lacasa et al in March 2017 provided evidence for patients with AP who had a history of upper respiratory tract infection and positive serum serology for Mycoplasma pneumonia [29]. In his report, Lacasa depended on the rule by Parenti et al [8], formulated in his intensive review about infectious causes of AP, where Parenti states that serological tests alone are not enough and that patients must show characteristic symptoms of the causative organism to avoid false association with AP.…”
Section: Bacterial Causes Of Apmentioning
confidence: 99%
“…The direct type is caused by bacteria in the blood stream triggering the release of local inflammatory mediators, while the indirect one is the result of a systemic hypercoagulable state. The real pathological mechanism, however, is unknown [29]. …”
Section: Pathogenesis Of Ap Caused By Infectious Microorganismsmentioning
confidence: 99%
“…Mycoplasma pneumoniae is one of the most common bacteria associated with infectious AP [138,139]. This microorganism produces multiple extra-pulmonary manifestations, including AP.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…Se han documentado manifestaciones digestivas como hepatitis, pancreatitis [ 172 , 173 , 174 ] y gastroenteropatía pierde proteínas [ 175 ]. A nivel musculoesquelético, se ha aislado en artrosis [ 176 ], miositis [ 177 ] y rabdomiólisis [ 178 ].…”
Section: Especies Implicadas En Patología Humanaunclassified